2020
DOI: 10.14731/kjis.2020.08.18.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Motives in Northeast Asian Aid Allocations: China, Japan, and Korea as a Collective Group and as Individual Donors

Abstract: The landscape of global foreign aid is changing with the growing number of new donors, especially in Asia. While Japan is no longer overwhelmingly dominant, complexity grows as China is becoming increasingly influential as an emerging donor, and Korea is rising to be a considerable donor by joining the OECD's Development Assistance Committee. In this context, there have been numerous controversies concerning East Asian donors, and even debates about the East Asian model of aid apart from the more traditional W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Despite somerecently expanding-references to 'South-South cooperation' in Rwandan policy documents, for instance, existing research suggests that Rwandans tend to perceive China not as 'Southern' but as an Asian partner-similar to DAC members Japan and Korea-that acts in a supply-driven way and with a strong focus on tangible 'win-win' results, such as infrastructure delivery (Grimm et al, 2011, 54f;see Grimm, 2015). This resonates with broader debates about (East) Asian development cooperation models that cut across traditional 'North-South' divisions and thus challenge the relevance of mainstream terminology (see Sohn et al, 2020;Stallings & Kim, 2016).…”
Section: Bilateral Frames: Cooperation Beyond ' South-south'mentioning
confidence: 74%
“…Despite somerecently expanding-references to 'South-South cooperation' in Rwandan policy documents, for instance, existing research suggests that Rwandans tend to perceive China not as 'Southern' but as an Asian partner-similar to DAC members Japan and Korea-that acts in a supply-driven way and with a strong focus on tangible 'win-win' results, such as infrastructure delivery (Grimm et al, 2011, 54f;see Grimm, 2015). This resonates with broader debates about (East) Asian development cooperation models that cut across traditional 'North-South' divisions and thus challenge the relevance of mainstream terminology (see Sohn et al, 2020;Stallings & Kim, 2016).…”
Section: Bilateral Frames: Cooperation Beyond ' South-south'mentioning
confidence: 74%
“…Relatedly, there is a large body of literature on the determinants of China's aid. In summary, it is often argued that China's provision of foreign aid is primarily driven by 1) the policy and economic interests of aid donors [19][20][21][22][23] and 2) the developmental needs of recipients ( [24,25]). Besides, some research also demonstrated these cross-border projects are normally driven by complementary needs, interests, and capabilities between the donor and recipient countries [20,23].…”
Section: Methodsmentioning
confidence: 99%
“…In summary, it is often argued that China's provision of foreign aid is primarily driven by 1) the policy and economic interests of aid donors [19][20][21][22][23] and 2) the developmental needs of recipients ( [24,25]). Besides, some research also demonstrated these cross-border projects are normally driven by complementary needs, interests, and capabilities between the donor and recipient countries [20,23]. Based on this literature, we make a hypothesis that the policy of China and the development needs of the recipients separately are two main drivers of China's building aid regarding the main architectural types and then try to validate this assumption by regression analysis in this research.…”
Section: Methodsmentioning
confidence: 99%
“…This means that the description of Korea's motives relative to Japan will shift depending on which motives are assigned to which explanatory variables (see Atkinson, 2018). For example, Sohn et al (2020, p. 123) found:
on an individual country level, economic motives are the primary determinants of aid allocations only for China. Japan prioritizes humanitarian factors over economic ones, and Korea does not reveal a clear pattern either way.
…”
Section: What Do We Know About South Korean Oda Motives?mentioning
confidence: 99%